Book-dress, bearskin, and wings: queer bodies and sideways growth in Das Leben der Hochgräfin von Rattenzuhausbeiuns - Rogers, Hannah Marie Elizabeth (Kansas State University, 2018)
In Das Leben der Hochgräfin von Rattenzuhausbeiuns, written by Bettina von Arnim and Gisela von Arnim Grimm, the material used to dress the bodies of young girls is unexpected and non-traditional. There are characters clothed in dresses made from the pages of books, bearskin coats, butterfly wings, onion root wigs, and many other bizarre materials. The main protagonist, Gritta, experiences, what Katheryn B. Stockton conceptualizes as “sideways growth,” or a non-linear, non-heteronormative childhood. The initial book-dress foreshadows the developmental possibilities for the protagonist Gritta. In this paper I argue that the text uses clothing made of non-traditional materials to construct queer girlhood for the female characters, and in doing so provides possible paths of “sideways growth.”
Keywords: Body; Clothing; Dress; Gritta; GirlhoodQueer